MULTITASKING REAL-TIME SCHEDULING IN A ROBOT (International Journal of Engineering and Computer Science, 2015)
This paper deals with loading artificial functions to a robot based on scheduling. Here, scheduling is the one which is used to avoid the delay between appplications. Based on RTOS scheduling has been done. Using zigbee communication the indications are given to the monitoring section. The semantic time scheduling is done to run all applications at a time without any time delay. The paper involves two sections 1. Robot module and  2. Monitoring section. The robot section deals with the data receiving from sensor nodes without any delay. The robotic section runs with RTOS and LPC2929 and acts as master node to which sensors are connected. In the monitoring section the data will be received  from the sensor nodes .